Adat Turun Tanah Bagi Suku Jawa Di Kota Palangka Raya Ditinjau Dari Prespektif Islam - Miftahul, Miftahul (IAIN Palangka Raya, 2015)
This study took place in the cit y of. This research is a custom object off the ground for Javanese